Role of galectin 3 and epicardial fat thickness in the development of atrial fibrillation in patients with metabolic syndrome - V. A. Ionin; O. V. Listopad; S. E. Nifontov; E. I. Baranova; A. V. Soboleva; E. V. Shlyakhto (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Objective. To evaluate the epicardial fat thickness (EFT) in patients with metabolic syndrome (MS), including paroxysmal and persistent atrial fibrillation (AF). To relate EFT to the fibroid heart marker, i.e. galectin 3. Materials and methods. We examined 100 patients with MS (50 with AF), and 50 healthy persons made the control group. Serum galectin 3 was measured by ELISA method. The EFT was measured with echocardiography. Results. EFT in patients with MS was twofold higher than in healthy persons. EFT in patients with MS and AF didn't differ significantly from that in patients with MS without AF. Positive correlation between the levels of EFT and galectin 3 in serum was revealed. Serum galectin 3 and EFT were associated with atrial fibrillation in patients with MS (OR:1,27, 95% CI 1,02-1,58 and OR:1,73, 95% CI 1,37-2,19, correspondingly).Conclusion. Definition of EFT at echocardiography can be used in the assessment of risk AF in patients with MS.